2015
DOI: 10.14257/ijunesst.2015.8.2.31
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Structure and Performance of Shea Butter Market in Bosso and Borgu Local Government Areas of Niger State, Nigeria

Abstract: Inefficiency in Shea butter marketing is one of the major challenging phases in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
4
5
0
Order By: Relevance
“…Furthermore, OEI of all types of market participants was higher than 100% implying that at all stages, marketers operated efficiently. This finding was consistent with the result obtained by Garba et al [12], in which shea butter market was determined to be efficient, with a ratio of marketing efficiency for all marketer groups greater than 100 percent. Among traders, wholesalers/brokers had the highest ratio of OEI (226.68%), indicating that maximization of the rate of output in terms of value added to input in terms of marketing costs was recorded by this group, leading to the most efficient business operation for this group.…”
Section: Operational Efficiency By Type Of Market Participantssupporting
confidence: 92%
“…Furthermore, OEI of all types of market participants was higher than 100% implying that at all stages, marketers operated efficiently. This finding was consistent with the result obtained by Garba et al [12], in which shea butter market was determined to be efficient, with a ratio of marketing efficiency for all marketer groups greater than 100 percent. Among traders, wholesalers/brokers had the highest ratio of OEI (226.68%), indicating that maximization of the rate of output in terms of value added to input in terms of marketing costs was recorded by this group, leading to the most efficient business operation for this group.…”
Section: Operational Efficiency By Type Of Market Participantssupporting
confidence: 92%
“…The bark is used to suppress cough and also to treat leprosy (Ferry et al, 1974). Shea nut contains about 60% fat and together with the oil palm serve as sources of edible oil for many households in many parts of the Sahel Africa, particularly Northern Nigeria (Ademola et al, 2012;Garba et al, 2015). Shea butter is well known for its use as a component of cosmetic formulations (Maranz et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Shea butter is well known for its use as a component of cosmetic formulations (Maranz et al 2004). However, reports from Ghana (Issahaku et al, 2011) through Republic of Benin (Honfo et al, 2011) to Nigeria (Ademola et al, 2012;Garba et al, 2015) affirms the production of Shea butter mainly through traditional methods passed down through generational line. Results from this present study revealed that all the sampled Shea butter contain loads of microbial contaminants compared to the branded Shea butter sample used in the study which showed no microbial growth.…”
Section: Resultsmentioning
confidence: 99%
“…Additional means could help in improving the quality, as in the control and certification of shea products [32], although certification is costly and requires consumers to bear part of the cost. Interestingly, our study shows that the additional cost to ensure the quality of the shea butter would be covered by a premium to be paid by the consumers.…”
Section: Discussionmentioning
confidence: 99%